Effect of nursing care by using Extended Nursing Care Model on quality of life of patients after coronary artery bypass graft - Jyoti M Chaudhari; Sankarsan Pani; Anuradha Mhaske; Anvay Mulay (MGM Journal of Medical Sciences, 2022)
Background: Though coronary artery bypass graft (CABG) is a life-saving surgery and a standardized procedure, the aim of the surgery is survival with quality of life (QOL). The extended role of the nurse was well recommended in community and clinical settings with the support of multidisciplinary team for safe care. The Extended Nursing Care Model (ENCM) provides the framework to facilitate early recovery and thereby improve the QOL and overall productivity after CABG. Aim and Objective: The aim of this article is to compare the difference in QOL of CABG patients with and without ENCM. Materials and Methods: Quasi-experimental Time Series Design with Comparison Group was used to study the effectiveness of ENCM. Among CABG patients enrolled on the day of admission with non-probability purposive sampling technique, 140 patients were randomly and equally distributed in the study and control groups on the day of discharge for recovery management. Generic EQ-5D-5L scale and MacNew Heart Disease-related QOL (MNHDRQOL) questionnaire were used to collect data at frequent intervals. The data obtained successfully from 69 patients in the study group and 63 patients in the control group were analyzed by using SPSS-21 Statistical Software, Mann–Whitney U-test, and Wilcoxon signed-rank test. Results: There was an improvement in the EQ-5D-5L score and MNHDRQOL score from baseline (before surgery) to 6th week and 12th week after surgery. This difference is statistically higher in the study group than in the control group (P <0.05) in all five domains of Euro QOL and all three domains of MNHDRQOL. Conclusion: Nursing care provided by using ENCM is effective in improving the QOL of CABG patients.